Mitigating the negative effect of air traffic controller mental workload on job performance: the role of mindfulness and social work support - Alaydi, Bader; Ng, Siew-Imm (MDPI, 2024)
Air traffic controllers (ATCOs) play a substantial part in securing the safety of flights, such that a compromise of the ATCOs’ performance may lead to tragedies. Given the mental workload that comes with the nature of ATCOs’ work, this study intends to investigate the impact of mental workload on ATCOs’ job performance and identify conditional factors that could mitigate the mental workload–ATCOs’ job performance relationship. Underpinned by the job demands–resources theory, a framework was developed to investigate the impact of job demands (mental workload) on job performance and whether personal resources (mindfulness and social work support) weaken the relationship. A total of 324 ATCOs across Saudi Arabia responded to the questionnaire. There were three notable findings. First, mental workload was indeed found to bring detrimental effects to ATCOs’ job performance. Second, mindfulness played a mitigating role, where more mindful ATCOs demonstrated less workload effect on performance. Thirdly, social work support also played a mitigating role, where ATCOs who perceived receiving greater job support experienced less detrimental impact from the workload on performance. This study verified the negative linkages between mental workload and job performance and identified the boundary conditions (mindfulness and social work support) that weaken the relationship. The limitations and future research directions are then discussed.